2022
DOI: 10.3389/frsus.2022.980047
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Engaging the citizen in the circular economy: Transcending the passive consumer role

Abstract: The transition to a resource-efficient and effective circular economy (CE) requires the active engagement of all societal and economic actors, including business, civic society, and political actors. Research, so far, has mainly focused on business solutions and policy approaches that enable these solutions. However, very little knowledge has been developed regarding the role of citizens in the CE (e.g., sharer, repairer, or buyer of quality products or second-hand products) and the transformations to everyday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In such a setting, customers-as in the classical understanding of consumers of products and services offered by industry-have responsibility and are integral parts of a bigger system, requiring a shift away from the "customer is king" paradigm. Counter to the current focus in literature on how customer behavior and preferences influence the emergence of circular business models (Gomes et al, 2022;Mostaghel & Chirumalla, 2021), the integral functions of customers need investigation (Milios, 2022) especially in regard to help reducing complexity in circular systems.…”
Section: Changing Role Of Customers: From Kings To Servantsmentioning
confidence: 99%
“…In such a setting, customers-as in the classical understanding of consumers of products and services offered by industry-have responsibility and are integral parts of a bigger system, requiring a shift away from the "customer is king" paradigm. Counter to the current focus in literature on how customer behavior and preferences influence the emergence of circular business models (Gomes et al, 2022;Mostaghel & Chirumalla, 2021), the integral functions of customers need investigation (Milios, 2022) especially in regard to help reducing complexity in circular systems.…”
Section: Changing Role Of Customers: From Kings To Servantsmentioning
confidence: 99%
“…Seven papers were identified that do attempt to summarise types of user/consumer behaviours. These papers discuss 'behaviours' in terms of broad categories (Gomes et al, 2022;Selvefors et al, 2019;Wastling et al, 2018), the different 'roles' that consumers/user may adopt (Maitre-Ekern, 2019;Milios, 2022), or types of circular 'strategies' (Camacho-Otero et al, 2020;Chamberlin, 2018). These papers do not, however, adopt a specific behavioural lens.…”
Section: The Benefits Of a Behavioural Approachmentioning
confidence: 99%
“…As Milios (2022) observes, the terms we use affect our thinking, and so we begin this section with some notes on language, before exploring existing attempts to define user circular behaviours. Firstly, we note that 'circular economy' is a heterogeneous, and umbrella, term (Garcia et al, 2021) bringing together a number of different ideas that centre around reframing the way resources are used and managed (Wastling et al, 2018).…”
Section: Current Understandings Of User Circular Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving toward a CE model, which signifies a closedloop production-consumption process and system, and its implementation requires systemic thinking, top-down and bottomup approach, initiatives and action, and the active involvement of various stakeholders, including the public and private sectors, and civil society (Kyriakopoulos et al, 2019;Calisto Friant et al, 2020;Desing et al, 2020). Various roles of citizens, individual engagement toward this transformation, and gaps in the existing knowledge highlight the need for bringing about changes in everyday life attitudes and behaviors for adopting a new way of thinking and for developing new competencies and skills (Milios, 2022). Furthermore, the European Union's (EU's) relevant policy framework includes the citizens' empowerment by providing trustworthy information (EU, 2020).…”
mentioning
confidence: 99%